Restorative Justice Kasus Kekerasan Dalam Rumah Tangga Ranah Pengadilan Militer Perbandingan Penerapan Restorative Justice Pengadilan Sipil - Aurel Muhammad Abdi Mahardhika; Muhammad Ghaffaar Irsyad Sumarsono Jr; Reina Azzahra Siregar; Fathiya Nur Rosyida (Jurnal Hukum Lex Generalis, 2025)
Domestic violence is a long-standing issue in Indonesia, governed by Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence. This research examines the implementation of restorative justice regulations in domestic violence cases within the military jurisdiction. The concept of restoring the original state in a criminal offense is manifested through a legal mechanism known as Restorative Justice. The objective of this study is to analyze the implementation of restorative justice in domestic violence cases within the military criminal justice system, in comparison to the civilian criminal justice system in Indonesia. Furthermore, it aims to analyze the alignment of restorative justice implementation in domestic violence cases with the principles of justice for both victims and perpetrators.